Balance hídrico como medio de gestión del uso del agua para mejorar la productividad en el cultivo de banano (Musa Paradisiaca) en el Ecuador. - Gamboa Barrio, Anthony Alexander (2024)
Water balances are performed using real or simulated precipitation data and climate information to calculate the water needs of a specific area; There are different types of water balance: climatic, agroclimatic, hydrological, agroforestry, basin, drainage and irrigation. This research was developed as a non-experimental component of a bibliographic nature, through a technique of analysis, synthesis and summary of the information obtained. From what was previously detailed, it was determined that the water balance allows the integration of climatic variables to determine irrigation needs during a period of time in order to plan, design or operate the availability of water in a given area. The water balance is one of the most important aspects, since it directly affects the growth and development of the banana crop. The factors that affect the water balance of banana cultivation are diverse and vary depending on the region and time of year; Two of the main factors are: precipitation and temperature. To determine the water balance, it is necessary to know the water contribution (irrigation (R), measured in volume) and the water yield of the crop (estimated evapotranspiration (ETc), water loss) due to evaporation of any evapotranspiration surface plus transpiration. of the banana crop and through drainage (D), the amount of water that seeps into the soil by gravity. The amount of water required for the ideal growth and good development of the organs in banana cultivation is 2000 mm wide sheets, taking into account the average temperature of 27 degrees, the average amount of daily irrigation is 5.5 mm.